2017
DOI: 10.1111/apha.12895
|View full text |Cite
|
Sign up to set email alerts
|

Isopimaric acid – a multi‐targeting ion channel modulator reducing excitability and arrhythmicity in a spontaneously beating mouse atrial cell line

Abstract: Low concentrations of IPA reduced the action potential frequency and restored regular firing by altering the voltage dependencies of several voltage-gated ion channels. These findings can form the basis for a new pharmacological strategy to treat atrial fibrillation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
25
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 58 publications
2
25
0
Order By: Relevance
“…The data in panel (e) were computed based on a combination of all of these isopimaric acid‐induced changes. Note that these changes are still prominent after the two K + currents, I to and IKr, that strongly regulate repolarization are modified in accordance with the findings of Salari et al …”
supporting
confidence: 90%
See 3 more Smart Citations
“…The data in panel (e) were computed based on a combination of all of these isopimaric acid‐induced changes. Note that these changes are still prominent after the two K + currents, I to and IKr, that strongly regulate repolarization are modified in accordance with the findings of Salari et al …”
supporting
confidence: 90%
“…Although both paroxysmal (brief) and chronic atrial fibrillation (AF) were considered to be benign, the notable association between maintained AF and stroke has resulted in AF now being a target for surgical intervention (ablation) and/or drug therapy. An interesting, forward‐looking paper from the Elinder group in this issue of Acta Physiologica reveals novel pharmacological agents and principles that could be the basis for more effective antiarrhythmic therapies for AF. Salari et al .…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…SH accelerated the steady state inactivation of I Na.P , indicating that SH reduced sodium channel availability as well as cardiomyocyte excitability [16,17]. Furthermore, it has been reported that many tachyarrhythmias, such as atrial fibrillation, were often accompanied by increased myocardial excitability, suggesting that the sodium channel may be an effective target for treating such tachyarrhythmias [18,19]. Thus, the reduced sodium channel availability by SH revealed that SH possessed great possibility to alleviate atrial fibrillation.…”
Section: Effects Of Sh On the Amplitude Of I Krmentioning
confidence: 99%